From Maternal Diet to Neurodevelopmental Disorders: A Story of Neuroinflammation - Bordeleau, Maude; Fernández de Cossío, Lourdes; Chakravarty, M. Mallar; Tremblay, Marie-Ève (Frontiers in Cellular Neuroscience, 2021)
Providing the appropriate quantity and quality of food needed for both the mother’s well-being and the healthy development of the offspring is crucial during pregnancy. However, the macro and micro-nutrient intake also impacts the body’s regulatory supersystems of the mother, such as the immune, endocrine, and nervous systems, which ultimately influence the overall development of the offspring. Of particular importance is the association between unhealthy maternal diet and neurodevelopmental disorders in the offspring. Epidemiological studies have linked neurodevelopmental disorders like autism spectrum disorders, attention-deficit-hyperactivity disorder, and schizophrenia, to maternal immune activation (MIA) during gestation. While the deleterious consequences of diet-induced MIA on offspring neurodevelopment are increasingly revealed, neuroinflammation is emerging as a key underlying mechanism. In this review, we compile the evidence available on how the mother and offspring are both impacted by maternal dietary imbalance. We specifically explore the various inflammatory and anti-inflammatory effects of dietary components and discuss how changes in inflammatory status can prime the offspring brain development towards neurodevelopmental disorders. Lastly, we discuss research evidence on the mechanisms that sustain the relationship between maternal dietary imbalance and offspring brain development, involving altered neuroinflammatory status in the offspring, as well as genetic to cellular programming notably of microglia, and the evidence that the gut microbiome may act as a key mediator.